Project Management Practices to Empower Lean Construction in Malaysia’s Construction Industry - Othman, Muhammad Izzuddin Syamil; Zainal, Rozlin; Kasim, Narimah; Abd Rahim, Mohd Hilmi Izwan (Research in Management of Technology and Business, 2023)
Construction industry is often viewed as problematic and inefficient. Lean Construction (LC) is one of practice to solve project management practice. Nevertheless, previous studies have found that Malaysia’s LC issues are a lack of management commitment, limited awareness of the concept, and a culture of resistance to change. Therefore, the objectives of this research are to identify the main problems of LC practices in construction project management and to identify the main solutions to empower LC practices in construction project management. This research focused on construction company G7 in Pahang as respondent and used a quantitative method to achieve all of objectives. This study surveys the 118 perceptions of Grade 7 contractors in Pahang. The respondents were given a questionnaire by face-to-face meeting and in a link of google form through WhatsApp and Email. A total of 81 (69%) respondents have given feedback in the questionnaire. Descriptive statistic by SPSS software was used to analyse the data for all objectives. This research found that the main problems and main solutions respectively insufficient training for workers and an internal management sponsor recorded as the highest frequency. This study may help G7 contractors adopt LC practises to successfully complete construction projects and advance the Malaysian construction industry.